Cooling rate as a process parameter in advanced roll forming to tailor microstructure, mechanical and corrosion properties of EN AW 7075 tubes. Issue 12 (14th December 2022) - Sajadifar, S.V.; Suckow, T.; Heider, B.; Oechsner, M.; Groche, P.; Niendorf, T.
Abstract: The effects of solution heat treatment parameters and quench media as a processing tool for tailoring microstructure, mechanical and corrosion properties in roll forming of EN AW 7075 alloy were studied. The highest yield stress and ultimate tensile strength were obtained for the specimens quenched in water, while the air‐cooled specimens exhibited inferior mechanical properties. Microstructural analysis of specimens showed that except water‐quenched specimens, the parts cooled/quenched in oil, in direct contact with tool steel and air are characterized by coarse precipitates and precipitate‐free zones. The corrosion tests showed that the cooling rate has a pronounced influence on the corrosion resistance and related mechanism of EN AW 7075 alloy. The surfaces of specimens quenched in water remained intact although pitting corrosion took place. The microstructure of the part processed by roll forming was explored in direct comparison. It is revealed that by the employment of quenching nozzles, a high cooling rate similar to the water‐quenched condition can be achieved. Results obtained in the present study pave the way to directly tailor aluminum parts for specific applications. Abstract : The analysis of mechanical properties, corrosion behavior and microstructure revealed that it is feasible to tailor EN AW 7075 parts in advanced processes, e. g. temperature assisted roll forming. Results obtained here revealed that a cooling rate close to the water‐quenched condition can be reached in the advanced thermomechanical process in focus.